EFL Students’ Experiences in a Flipped Reading Comprehension Classroom - Silvia Ramadhanty; Nina Puspitaloka (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The aim of this research is to investigate EFL students’ experiences that appear in EFL students during the application of the flipped classroom learning model. The research was conducted by using a qualitative approach and descriptive method. The research participants were nine first-grade students at one of the public senior high school in Karawang. The participants were divided into three groups: three low-level students, three middle-level students, and three high-level students. To collect the data, researchers used were observation, interview, and documentation. This research found that the application of a flipped classroom provided positive experiences for students. The use of the video in this learning model made students excited. However, the use of online flipped classrooms appeared several challenges such as students must have internet access while they were learning and the internet connection, they have must be stable so that learning activities run well.